Analysis and implementation of the impact of change: application to heterogeneity algorithms in enterprise architecture - Jihane Lakhrouit; Karim Baïna (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Measurements play an important role in many scientific fields in general and intheanalysisofenterprisearchitectureinparticular.In software engineering, the measures are used to control the quality of the software product and better manage development projects to control the cost of production.In this article we proposed firstly models and measures to evaluate and analyze the complexity of the enterprise architecture and especially the heterogeneity of components and relationships, and secondely we developed a model to automatically detect the change of measures and their impact on enterprise architecture.